BNP but Not s-cTnln is associated with cardioembolic aetiology and predicts short and long term prognosis after cerebrovascular events. - Nicole Nigro; Karin Wildi; Christian Mueller; Philipp Schuetz; Beat Mueller; Felix Fluri; Mirjam Christ-Crain; Mira Katan (PLoS ONE, 2014)
We analyzed the prognostic value of b-type natriuretic peptide (BNP) and sensitive cardiac Troponin (s-cTnI) in patients with ischemic stroke or transient ischemic attack (TIA) and their significance in predicting stroke aetiology.In a prospectively enrolled cohort we measured BNP and s-cTnI levels upon admission. Primary endpoints were mortality, unfavorable functional outcome and stroke recurrence after 90 days and after 12 months. Secondary endpoint was cardioembolic aetiology.In 441 patients BNP but not s-cTnI remained an independent predictor for death with an adjusted HR of 1.2 (95% CI 1.1-1.4) after 90 days and 1.2 (95% CI 1.0-1.3) after one year. The comparison of the Area under Receiver Operating Characteristic (AUROC) of model A (age, NIHSS) and model B (age, NIHSS, BNP) showed an improvement in the prediction of mortality (0.85 (95% CI 0.79-0.90) vs. 0.86 (95% CI 0.81-0.92), Log Rank p = 0.004). Furthermore the category free net reclassification improvement (cfNRI) when adding BNP to the multivariate model was 57.5%, p<0.0001. For the prediction of functional outcome or stroke recurrence both markers provided no incremental value. Adding BNP to a model including age, atrial fibrillation and heart failure lead to a higher discriminatory accuracy for identification of cardioembolic stroke than the model without BNP (AUC 0.75 (95% CI 0.70-0.80) vs. AUC 0.79, (95% CI 0.75-0.84), p = 0.008).BNP is an independent prognostic maker for overall mortality in patients with ischemic stroke or TIA and may improve the diagnostic accuracy to identify cardioembolic aetiology.ClinicalTrials.gov NCT00390962.